(untitled) (Research, Society and Development, 2025)
Early Childhood Caries (ECC) is a multifactorial condition affecting primary teeth and is linked to behavioral, dietary, and social factors. This article aims to analyze the long-term damage caused by ECC through a literature review. A qualitative and descriptive methodology was used, based on scientific articles indexed in SciELO, PubMed, BVS, and Google Scholar. The results show that untreated ECC compromises the physical, social, and emotional development of children, negatively affecting their quality of life. It is concluded that preventive measures, such as family guidance and early dental care, are essential to minimize the impacts of ECC.